Temporal characteristics of L- and M-cone isolating steady-state electroretinograms - Kommanapalli, Deepika; Murray, Ian J.; Kremers, Jan; Parry, Neil R. A.; Mckeefry, Declan J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Cone isolating stimuli were used to assess the temporal frequency response characteristics of L- and M-cone electroretinograms (ERGs) in nine trichromatic and four dichromatic human observers. The stimuli comprised sinusoidal temporal modulations varying from 5 to 100 Hz. ERGs were recorded using corneal fiber electrodes and subjected to fast Fourier transform analysis. At low temporal frequencies (<10 Hz) the L- and M-cone ERGs had similar amplitude and exhibited minimal differences in apparent latency. At higher flicker rates (>20 Hz) L-cone ERGs had greater amplitudes and shorter apparent latencies than the M-cone responses. These differences between the L- and M-cone ERGs are consistent with their mediation by chromatic and luminance postreceptoral processing pathways at low and high temporal frequencies, respectively.
EVALuna2:21213